Assessing the Accuracy of Remotely Sensed Data: Principles and Practices - Congalton, Russell G. (CRC Press, 2009)
Because the accuracy of remotely sensed data is critical to any successful mapping project, accuracy assessment is an important tool for anyone who uses remote sensing.